Environmental Assessment of Polycyclic Aromatic Hydrocarbon Concentrations in Air at Thermal South Power Station of Baghdad - H. Afaj, Adnan; Shanshal, Muthna; M. H. Almousawi, Israa; Adnan A., Safauldeen (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Sixteen polycyclic aromatic hydrocarbons (PAHs) concentrations were measured in aerosol samples collected for the period from April 2012 to February 2013 at thermal south power station of Baghdad. Fourty one aerosol sample were extracted with (1:1) dichloromethane and methanol using soxhlet for seventeen hour. The extraction solution was analyzed applying GC/MS. The PAH concentrations outside thermal south power station were higher than those inside it, and higher in summer season than in winter. Naphthalene, pyrene, Anthracene, Indeno [1, 2, 3-cd] pyrene and Phenanthrene were the most abundant PAHs detected in all points at the site sampling. The total polycyclic aromatic hydrocarbon (TPAH) and total suspended particles (TSP) concentrations were measured during the measurement period. For individual PAH compounds, the results showed a strong correlation with each other (0.998 - 0.77) at both sites.